OPTIMALISASI PANGAN LOKAL UNTUK MENCEGAH STUNTING “INOVASI KUE KERING SAGU KELOR (KUSAKE)” DI WILAYAH KERJA PUSKESMAS RIDGE KABUPATEN BIAK NUMFOR - Hermayani; Selina. Boseren; Selpiana Tonapa; Janeth Makmaker; Fitriani (Health Care : Journal of Community Service, 2025)
Stunting is a growth and development disorder characterized by a low height-for-age (H/A) index, with a Z-score less than -2 SD based on the WHO growth standards. This condition is caused by chronic malnutrition over a prolonged period and is influenced by both direct factors, such as inadequate nutrient intake, and indirect factors, such as suboptimal childcare practices. One of the key strategies for stunting prevention is nutritional intervention using locally available, nutrient-rich foods. Sago and moringa are two local food sources with great potential, offering a synergistic combination of energy (from sago) and micronutrients (from moringa). Processed products such as sago-moringa cookies provide a nutritious, affordable, and culturally acceptable food alternative. This community service activity aims to improve the knowledge and skills of pregnant women and mothers of toddlers in processing local food ingredients to prevent stunting. The method used was educational outreach focusing on the benefits of consuming sago-moringa cookies. The results of this activity showed an increase in the knowledge and skills of the target participants in utilizing local food as a preventive measure against stunting, while also supporting local food security and community economic empowerment.